Retrofitting Multi-Period Heat Exchanger Networks using the Reduced Superstructure Synthesis Approach - Adeniyi J. Isafiade (Chemical Engineering Transactions, 2018)
In this paper, the reduced superstructure synthesis method is applied to the retrofit of heat exchanger networks involving multi-period operations. The first step in the synthesis procedure entails solving the multi-period problem to obtain a grass-root solution using the existing multi-period stage-wise superstructure synthesis method. The second step entails the generation of the reduced multi-period superstructure using a combination of two sets of matches as the initialising binary variables. These matches include those selected in the grass-root solution of the first step and those that exist in the original network. The generated reduced superstructure of this second step is then solved as a mixed integer non-linear programming model to obtain a final retrofitted network. The solution obtained from the case study considered in this paper compares favourably with what was reported in the literature.